2020
DOI: 10.3390/ijms21207567
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Melanoma Cells Deliver microRNAs to Dendritic Cells and Cytotoxic T Lymphocytes through Connexin-43 Channels

Abstract: Alterations in microRNA (miRNA) profiles, induced by tumor microenvironment stressors, like hypoxia, allow cancer cells to acquire immune-resistance phenotypes. Indeed, hypoxia-induced miRNAs have been implicated in cancer progression through numerous cancer cell non-autonomous mechanisms, including the direct transfer of hypoxia-responsive miRNA from cancer to immune cells via extracellular vesicles. Connexin-43 (Cx43)-constituted gap junctions (GJs) have also been involved in miRNA intercellular mobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 74 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…In contrast, tumor cell proliferation can be inhibited by anti-tumor effect of CD8-positive T cells and their activities (Mahmoud et al, 2017;Pio et al, 2019). The role of hypoxia in immune escape has been identified (Barsoum et al, 2014;Li et al, 2018;Zou et al, 2018;Liu and Curran, 2020;Tittarelli et al, 2020;Van Duijn et al, 2022). For metastasis, melanoma needs to adapt to microenvironmental changes.…”
Section: Original Articlementioning
confidence: 99%
“…In contrast, tumor cell proliferation can be inhibited by anti-tumor effect of CD8-positive T cells and their activities (Mahmoud et al, 2017;Pio et al, 2019). The role of hypoxia in immune escape has been identified (Barsoum et al, 2014;Li et al, 2018;Zou et al, 2018;Liu and Curran, 2020;Tittarelli et al, 2020;Van Duijn et al, 2022). For metastasis, melanoma needs to adapt to microenvironmental changes.…”
Section: Original Articlementioning
confidence: 99%
“…Additionally, miR-9 overexpression in DCs reduced tumor progression in a melanoma mouse model. miR-192-5p- and miR-148a-3p-derived hypoxic melanoma cells were transferred into DCs by the Cx43 channel and miR-192-5p was delivered to both DCs and T cells to inhibit their functions [ 85 ].…”
Section: Role Of Mirnas In the Tumor Microenvironmentmentioning
confidence: 99%
“…A previous study demonstrated that miR-498 and miR-3187-3p in melanoma-derived exosomes reduces the functions of CD8+ T cells by targeting IFN-α and protein tyrosine phosphatase receptor type C (PTPRC), the coding gene for CD45, respectively [ 105 ]. Hypoxic melanoma cells deliver miR-192-5p to cytotoxic T cells via Connexin-43 (Cx43)-constituted gap junctions to reduce the T cell functioning [ 85 ].…”
Section: Role Of Mirnas In the Tumor Microenvironmentmentioning
confidence: 99%
“…Melanoma cells can form GJCs with themselves and with fibroblasts, but do not with keratinocytes (Hsu et al, 2000), supporting the idea that Cx deregulation has a huge impact on the homeostatic control that keratinocytes exert over melanocytes. Moreover, melanoma cells establish GJIC with immune cells, such as natural killer (NK) cells, T cells, and dendritic cells (DCs), indicating that the immune system also controls melanoma progression by Cx-mediated mechanisms (Saccheri et al, 2010;Tittarelli et al, 2014;Gleisner et al, 2017;Hofmann et al, 2019;Tittarelli et al, 2020;Navarrete et al, 2020). Several proteins that allow cellto-cell communication have been described as key factors in tumor cell transformation.…”
Section: Mel Anomamentioning
confidence: 99%